Anxiety Disorders and Gender - Stein, Dan J (Springer, 2015)
Anxiety and related disorders are common conditions that disproportionately affect women. In this book, the epidemiology, psychobiology, diagnosis, evaluation, pharmacotherapy and psychotherapy of major anxiety and related disorders are examined with special reference to the effects of gender and sex on clinical presentation and treatment. The conditions considered include generalized anxiety disorder, obsessive-compulsive disorder, panic disorder, posttraumatic stress disorder and social anxiety disorder. In addition, the management of anxiety and related disorders during pregnancy and lactation are discussed. Two concluding chapters specifically address anxiety disorders in women and in men, summarizing key points for clinicians and researchers. The authors are leading clinicians, including both psychiatrists and psychologists, from around the globe.